Control of Palmer amaranth (Amaranthus palmeri) and common waterhemp (Amaranthus rudis) in double crop soybean and with very long chain fatty acid inhibitor herbicides - Hay, Marshall Mark (Kansas State University, 2017)
During 2015 and 2016, five site years of research were implemented in double crop soybean after winter wheat at experiment fields in Kansas near Manhattan, Hutchinson, and Ottawa to assess various non-glyphosate herbicide treatments at three different application timings for control of Palmer amaranth (Amaranthus palmeri S. Wats.) and common waterhemp (Amaranthus rudis Sauer). Spring-post (SP) treatments with residual control of Palmer amaranth and waterhemp were applied in the winter wheat at Feekes 4 and resulted in less than 50% control of Palmer amaranth and waterhemp at the time of double crop soybean planting. Pre-harvest treatments were applied two weeks before winter wheat harvest. 2,4-D resulted in highly variable Palmer amaranth and waterhemp control whereas flumioxazin resulted in comparable control to PRE treatments that contained paraquat plus a residual herbicide. Excellent Palmer amaranth and waterhemp control was observed at 1 week after planting (WAP) double crop soybean with a preemergence (PRE) paraquat application; however, reduced control of Palmer amaranth and waterhemp was noted at 8WAP due to extended emergence. Palmer amaranth and waterhemp control was 85% or greater at 8WAP for most PRE treatments that included a combination of paraquat plus residual herbicides. PRE treatments that did not include the combination of paraquat and residual herbicides did not provide acceptable control. A second set of field experiments were established in 2015 and 2016 near Manhattan, Hutchinson, and Ottawa to assess residual Palmer amaranth and waterhemp control with very-long-chain-fatty acid (VLFCA) inhibiting herbicides. Acetochlor (non-encapsulated and encapsulated), alachlor, dimethenamid-P, metolachlor, S-metolachlor, and pyroxasulfone as well as the microtubule inhibiting herbicide pendimethalin were applied at three different field use rates (high, middle, and low) based on labeled rate ranges for soybean as PRE treatments in a non-crop scenario after the plot was clean tilled with a field cultivator. The experiment was conducted one time in 2015 and four times in 2016 at two different locations for a total of five site years of data. PRE applications were made June 1, 2015, near Manhattan. PRE applications in 2016 were made in April at locations near Hutchinson and Ottawa; the second run of the experiment was applied in June at the same locations on a different set of plot areas. At Manhattan pyroxasulfone, S-metolachlor, and dimethenamid-P resulted in the highest Palmer amaranth control at 4WAT. At Hutchinson, pyroxasulfone resulted in superior Palmer amaranth control compared to dimethenamid-P and pendimethalin at 4WAT and 8WAT. At Ottawa, acetochlor, S-metolachlor, and pyroxasulfone resulted in higher waterhemp control than alachlor and pendimethalin at 4WAT and 8WAT.
Keywords: Herbicide; Paraquat; Chloracetamide; VLCFA; SoybeanPigweed